Evaluasi Kebijakan Pelayanan Kesehatan Oleh Puskesmas Sebagai Street Level Bureaucracy di Masa Pandemi Covid-19 - Nikki Prafitri (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2022)
Policy evaluation is an effort to provide an assessment of policy results to become input and recommendations for policymakers. The Covid-19 pandemic has brought about significant changes in the implementation of policies, especially health service policies. Health care policies need to adapt to pandemic conditions and social restrictions. Puskesmas as a street-level bureaucracy play an important role to carry out health services optimally. The Cipocok Jaya Health Center as the locus of this research experienced a decline in the quality of health services based on the community satisfaction index during the Covid-19 pandemic. The purpose of this study was to evaluate health services at the Cipocok Jaya Public Health Center as a street-level bureaucracy. The method used in this research is the qualitative method. The results showed that the health services provided by the Cipocok Jaya Health Center had not been running effectively due to the unpreparedness of human resources at the Puskesmas to adapt to the service model following the pandemic conditions. Other factors are the inadequate budget, facilities and infrastructure and the number of health workers as well as public awareness and readiness in adapting to services during the Covid-19 pandemic.